2018
DOI: 10.1007/s00520-018-4325-8
|View full text |Cite
|
Sign up to set email alerts
|

Positive mental health among cancer survivors: overlap in psychological well-being, personal meaning, and posttraumatic growth

Abstract: Purpose Positive mental health involves theoretical constructs like psychological well-being, personal meaning, and posttraumatic growth. This study aims to provide empirical insight into possible overlap between these constructs in cancer survivors. Methods Within the context of a randomized controlled trial, 170 cancer survivors completed the patient-reported outcome measures (PROMs) Ryff's Scales of Psychological Well-Being (SPWB), Personal Meaning Profile (PMP), and Posttraumatic Growth Inventory (PTGI). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…In this study, the total PTG score of 160 Chinese children with malignant tumors during the treatment was (41.64±15.3), which was lower than that of adults with cancers domestically and abroad [ 41 42 ], indicating that although 8~18 years old children with malignant tumors gained a certain degree of growth, the overall level was low, which may be related to their immature mind or incomplete cognitive development. Furthermore, it was found that there was a significant positive correlation between PTG and behavior problems of children with malignant tumors in the treatment period, and the correlation analysis showed that new possibility dimension had the greatest impact on the anxiety dimension ( r = -.387, P < .01).…”
Section: Discussionmentioning
confidence: 56%
“…In this study, the total PTG score of 160 Chinese children with malignant tumors during the treatment was (41.64±15.3), which was lower than that of adults with cancers domestically and abroad [ 41 42 ], indicating that although 8~18 years old children with malignant tumors gained a certain degree of growth, the overall level was low, which may be related to their immature mind or incomplete cognitive development. Furthermore, it was found that there was a significant positive correlation between PTG and behavior problems of children with malignant tumors in the treatment period, and the correlation analysis showed that new possibility dimension had the greatest impact on the anxiety dimension ( r = -.387, P < .01).…”
Section: Discussionmentioning
confidence: 56%
“…It may be that the social function of reminiscence and life review leads to improved self-esteem [ 15 ]. However, positive mental health is complex and involves various theoretical constructs [ 23 ]. Previous research showed that data from questionnaires on psychological well-being and personal meaning overlap to a large extent.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we utilised the personal growth subscale from Ryff’s (1989) Psychological Wellbeing Scales, which we considered analogous to post-traumatic growth. Previous research by Holtmaat et al (2019) has found that this subscale loads on the same factor as items used in one of the most common measures of post-traumatic growth, the Posttraumatic Growth Inventory (Tedeschi & Calhoun, 1996). This suggests that personal growth and post-traumatic growth are largely overlapping constructs, and therefore the personal growth subscale is an appropriate proxy measure.…”
Section: Methodsmentioning
confidence: 99%